Do we overlook predictive factors in Poseidon 1 patients? A retrospective analysis co-evaluating antral follicle counts & diameters - Gürkan Uncu; Kiper Aslan; Cihan Cakir; Berrin Avci; Isil Kasapoglu; Carlo Alviggi (BMC, 2024)
Abstract Background An unexpected impaired ovarian response pertains to an insufficient reaction to controlled ovarian hyperstimulation. This deficient reaction is identified by a reduced count of mature follicles and retrieved oocytes during an IVF cycle, potentially diminishing the likelihood of a successful pregnancy. This research seeks to examine whether the characteristics of antral follicles can serve as predictive indicators for the unexpected impaired ovarian response to controlled ovarian stimulation (COS). Methods This retrospective cohort study was conducted at a tertiary university hospital. The electronic database of the ART (assisted reproductive technologies) center was screened between the years 2012-2022. Infertile women under 35 years, with normal ovarian reserve [anti-Müllerian hormone (AMH) > 1.2 ng/ml, antral follicle count (AFC) > 5] who underwent their first controlled ovarian stimulation (COS) cycle were selected. Women with < 9 oocytes retrieved (group 1 of the Poseidon classification) constituted the group A, whereas those with ≥ 9 oocytes severed as control (normo-responders) one (group B). Demographic, anthropometric and hormonal variables together with COS parameters of the two groups were compared. Results The number of patients with < 9 oocytes (group A) was 404, and those with ≥ 9 oocytes were 602 (group B). The mean age of the group A was significantly higher (30.1 + 2.9 vs. 29.4 + 2.9, p = 0.01). Group A displayed lower AMH and AFC [with interquartile ranges (IQR); AMH 1.6 ng/ml (1-2.6) vs. 3.5 ng/ml (2.2-5.4) p < 0.01, AFC 8 (6-12) vs. 12 (9-17), p < 0.01]. The number of small antral follicles (2-5 mm) of the group A was significantly lower [6 (4-8) vs. 8 (6-12) p < 0.01), while the larger follicles (5-10 mm) remained similar [3 (1-5) vs. 3(1-6) p = 0.3] between the groups. Conclusion The propensity of low ovarian reserve and higher age are the main risk factors for the impaired ovarian response. The proportion of the small antral follicles may be a predictive factor for ovarian response to prevent unexpected poor results.